Pandemia jako portal – ujawniony potencjał transformacyjny rodziców w kryzysie pandemicznej edukacji. Studium przypadku polskiej publicznej szkoły podstawowej w pierwszej fali COVID-19 - Wiatr, Marta (Pedagogika Społeczna Nova, 2024)
Objective: The objective of the presented analysis is to shed light on the relationship between family and school through the lens of institutional-educational practices during the first wave of the COVID-19 pandemic. Background: From research on pandemic education during the first wave of COVID-19, a portrayal emerges of parents as obvious partners of the school in fulfilling educational tasks. However, parents are simultaneously depicted as a group heavily burdened with additional school-related responsibilities, incurring extraordinary costs as a result. This raises questions about the real and potential participation of parents in the organization of pandemic education, including the “power play” activated in crisis situations, shaping educational solutions during the first wave of the pandemic. Methodology: In this article, I draw upon qualitative participatory research conducted in June and July 2020 within the community of parents whose children attended an urban public elementary school. A case study method was employed. Qualitative analyses primarily encompassed data derived from responses provided by parents (N = 104) to open-ended questions in an electronic survey. Data from the electronic diary Librus and spontaneous statements from parent representatives were also utilized. Results: Analyses revealed the “play of different forces” influencing both the process of shaping new educational practices using distance learning tools and the relationships between participants in this“game” (school and parents). On one hand, a clear school-oriented vision of parents as an obvious and accessible resource supporting school tasks and practices emerged. On the other hand, parents revealed themselves as a dynamic transformative potential in relation to both school practices and the vision of relationships among participants in remote education conducted during the pandemic.